Night work, mortality, and the link to occupational group and sex - Torbjörn Åkerstedt; Jurgita Narusyte; Pia Svedberg (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVE: Night shifts are associated with several major diseases. Mortality has been studied only to a limited extent, and the association with night shifts remains unclear. The purpose of the present study was to investigate the association between duration of night shift exposure and mortality in a large sample from the Swedish Twin Registry (the SALT cohort). METHODS: Cox proportional hazards regression models were used to analyze the data (N=42 731) over a follow-up period of 18 years, with years of night shift work as the exposure variable and adjustment for lifestyle factors and age, and stratification on gender and occupational group. RESULTS: The hazard ratio (HR) for "ever" night shifts for total mortality was 1.07 [95% confidence interval (CI) 1.01-1.15] but 1.15 (95% CI 1.07-1.25) for longer exposure (>5 years). Also, HR for cause-specific mortality due to cardiovascular disease was significant, with higher HR for longer night shift exposure. Mortality due to cancer was significant for longer exposure only. White-collar workers showed significant HR for longer exposure. In particular, male white-collar workers showed a significant HR, with a highest value for longer exposure [HR 1.28 (95% CI 1.09-1.49)]. Heredity did not influence the results significantly. CONCLUSIONS: Long duration of exposure to night shift work is associated with increased mortality, particularly in male white-collar workers. The lack of effects of accumulated exposure suggests that the results should be interpreted with caution.